Relationship Between Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) and Other Financial Authorities - Anshori, Aiyub; Nurlia, Nurlia (Tujjar International Journal of Islamic Economics Development, 2023)
Historically, DSN-MUI is under the MUI structure that was officially established in 1998. DSN-MUI is an independent religious institution that does not have the authority to enact legal regulations directly in regulating Shariah banking activities. Furthermore, the DSN-MUI is an advisory body that is not under any financial authority. It is also not intervened by the state in issuing fatwa. Besides that, as DSN-MUI is not a state institution it is not involved in any form of legislation activities. However, DSN-MUI’s roles and functions have been legitimized through Law No 21 of 2008 pertaining to Islamic Banking implicitly. Therefore, this research seeks to identify the legal authority/status of Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) in Islamic Financial Institutions in Indonesia. The result of this research shows that DSN-MUI is an independent authority which is the main body in Shariah matters to determine and maintain the products, services, and operations in every Shariah business entity in carrying out the business on the right track. Nevertheless, there are implications of being an independent institution. Firstly, DSN-MUI is not bound by regulations to oversee financial institutions, the reason why there is no budget allocated to it by the government. Secondly, because DSN-MUI is not a legal authority it does not have the right to impose penalties on financial institutions which do not comply with Islamic law through fatwas. Likewise, DSN-MUI is unable to law enforce the fatwa to Islamic Financial Institutions, even though they play vital roles in IFIs in Indonesia since every business entity must be certified by DSN-MUI.